1980
DOI: 10.1007/bf00537293
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of the receptor potential with the light induced transient increase in intracellular calcium-concentration measured by absorption change of arsenazo III injected into Limulus ventral nerve photoreceptor cell

Abstract: The light-induced membrane voltage response (receptor potential, ReP) and the absorption change of the intracellularly injected calcium indicator arsenazo III (arsenazo response) were recorded simultaneously in Limulus ventral nerve photoreceptor cells. A double pulse technique was applied for stimulation. After pressure injection of the indicator into the cell absorption changes were measured at 646 nm to obtain a measure of the changes of the intracellular calcium ion concentration. 1. The size of the arsena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

1982
1982
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 13 publications
2
31
0
1
Order By: Relevance
“…Effect of Light Adaptation on the Light-induced Ca ; Increase J. E. Brown and Blinks (1974), using aequorin, and Maaz and Stieve (1980), using arsenazo 111, showed that the amplitude of the indicator response was related to the adaptational state of the cell . In those experiments, the state of adaptation was varied by changing the interstimulus interval for a pair of equally bright stimuli: the aequorin or the arsenazo signal elicited by the second stimulus of the pair became smaller as the interstimulus interval decreased.…”
Section: Table IVmentioning
confidence: 98%
See 1 more Smart Citation
“…Effect of Light Adaptation on the Light-induced Ca ; Increase J. E. Brown and Blinks (1974), using aequorin, and Maaz and Stieve (1980), using arsenazo 111, showed that the amplitude of the indicator response was related to the adaptational state of the cell . In those experiments, the state of adaptation was varied by changing the interstimulus interval for a pair of equally bright stimuli: the aequorin or the arsenazo signal elicited by the second stimulus of the pair became smaller as the interstimulus interval decreased.…”
Section: Table IVmentioning
confidence: 98%
“…Beyond this question, a controversy exists regarding the source of the Ca ions that gives rise to the light-induced Ca ; increase (J . E. Brown and Blinks, 1974 ;Lisman, 1976 ;Maaz and Stieve, 1980) . Here we present evidence that bathing the photoreceptors in low Ca.…”
Section: Table IVmentioning
confidence: 99%
“…Less elaborate, but also well developed, are Ca2+-sequestering sub-surface cisternae associated with the nonreceptive plasma membrane areas of the cell (43) . These two prominent high-affinity Ca"-buffering SER elements thus possess a strategic position relative to the cell periphery where stimulus-induced changes of Cai+ (6,8,9,26) most probably take place.…”
Section: Comparative Aspectsmentioning
confidence: 99%
“…The Ca pump has a high affinity for Ca 2+ ions : the threshold for activation of the pump is -5 X 10 -8 M, the apparent KM,c,, is -4 X 10 -7 M . When Na' or Li + is substituted for K+ , Ca uptake rate is decreased by 40-50% .The results show that the Ca t+ -sequestering SER in leech photoreceptors shares some basic properties with skeletal muscle sarcoplasmic reticulum and supports the idea that certain subregions of the SER in invertebrate photoreceptors function as effective Ca 2+ sinks/buffers close to the plasmalemma.Direct evidence from measurements with Ca 2+ indicators (6,8,9,26) and Ca'-sensitive microelectrodes (6), as well as indirect evidence from electrophysiological experiments (see, for example, references 1,15,24,25,35), suggest that the free calcium concentration (Caû,+) in the cytosol of photoreceptor cells of invertebrates increases upon illumination. Several laboratories have shown that this light-induced increase of Cap' modulates the adaptational state of the cells (see reference 7 for review), a Cat+-dependent potassium conductance (see, for example, reference 17, 18, 38), and mediates the light-induced pigment granule migration in fly photoreceptors (22) .…”
mentioning
confidence: 99%
See 1 more Smart Citation